2006
DOI: 10.1097/00000542-200606000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Complement C5a Receptor Reduces Incisional Allodynia, Edema, and Cytokine Expression

Abstract: The tissue directly surrounding incisions in mouse hind paws undergoes large changes in the content of specific cytokines in addition to demonstrating edema and nociceptive sensitization. By blocking the receptor for one component of the complement system, C5a, all of these changes can be reduced. Complement receptor inhibitors may constitute a novel group of compounds useful in reducing the pain and swelling of surgical incisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
117
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(128 citation statements)
references
References 58 publications
9
117
0
2
Order By: Relevance
“…Results for both paws were averaged. The C5a receptor (C5aR) antagonist, a synthetic cyclic AcF-[OPdChaWR] peptide, was produced by the MGH peptide core and stored at Ϫ80°C (0.5 mg/ml PBS and 5% ethanol) (Clark et al, 2006). A catheter (32 gauge; Recathco) was implanted into the intrathecal space of the vertebral column with its tip at the lumbar (L3-L5) level through a cisternal incision.…”
Section: Methodsmentioning
confidence: 99%
“…Results for both paws were averaged. The C5a receptor (C5aR) antagonist, a synthetic cyclic AcF-[OPdChaWR] peptide, was produced by the MGH peptide core and stored at Ϫ80°C (0.5 mg/ml PBS and 5% ethanol) (Clark et al, 2006). A catheter (32 gauge; Recathco) was implanted into the intrathecal space of the vertebral column with its tip at the lumbar (L3-L5) level through a cisternal incision.…”
Section: Methodsmentioning
confidence: 99%
“…A cut in the skin and subcutaneous tissues during the surgical incision causes damage to the tissues; this stimulates peripheral nociceptors resulting in pain sensation [7]. In addition, inflammation of the wound can arouse the nociceptors resulting in pain sensation [7,8]. Different short-or medium-acting sedatives, narcotics, and local anesthesia have been employed during the operation as an aide-de-camp to anesthesia or to alleviate postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that demonstrated the involvement of proinflammatory cytokines interleukin 1β (IL-1β) and tumor necrosis factor alpha (TNF-α) 9 , and the nerve growth factor (NGF) 10 in the induction and maintenance of pain in injured peripheral tissue (as found in surgeries). These proinflammatory substances play important roles in mediating exaggerated pain conditions 11 .…”
mentioning
confidence: 99%